A Trust-based Mechanism for Avoiding Liars in Referring of Reputation in Multiagent System - Manh Hung Nguyen, Dinh Que Tran ((IJARAI) International Journal of Advanced Research in Artificial Intelligence, Vol.4, No.2, 2015, 2016)
Trust is considered as the crucial factor for agents in decision making to choose the most trustworthy partner during their interaction in open distributed multiagent systems. Most current trust models are the combination of experience trust and reference trust, in which the reference trust is estimated from the judgements of agents in the community about a given partner. These models are based on the assumption that all agents are reliable when they share their judgements about a given partner to the others. However, these models are no more longer appropriate to applications of multiagent systems, where several concurrent agents may not be ready to share their private judgement about others or may share the wrong data by lying to their partners.